Pengaruh Penggunaan Facebook Terhadap Minat Berwirausaha Siswa Smk Guna Jaya Kecamatan Keritang Kabupaten Indragiri Hilir - Nuraisya, Nuraisya (Multidisciplinary Journal of Religion and Social Sciences, 2024)
This research aimed at knowing the effect of using Facebook to student entrepreneurial interest at Vocational High School of Guna Jaya, Keritang District, Indragiri Hilir Regency. This research was motivated by some students who did not use Facebook for entrepreneurship, as a place of promotion, and as media to find entrepreneurship sciences that have never been studied. This research used descriptive quantitative method. The samples of this research were 86 students form XI and XII grades. Questionnaire and documentation techniques were used for collecting the data. The data analysis technique used the tests of validity, reliability, normality, linearity, simple linear regression analysis and hypothesis. The results of this research obtained that robserved = 0.281 and rtable in significant level 5% (0.281 > 0.213). It means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. When robserved = 0.281 was compared with rtable in significant level 1% (0.281 > 0.278), It means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Therefore, there was a significant effect of using Facebook to student entrepreneurial interest at Vocational High School of Guna Jaya, Keritang District, Indragiri Hilir Regency.